An evaluation of active acoustic methods for detection of marine mammals in the Canadian Beaufort Sea. Issue 1 (14th July 2015) - Pyć, Cynthia D.; Geoffroy, Maxime; Knudsen, Frank Reier
Abstract: A commercially available fisheries sonar was mounted on an icebreaker and evaluated during an environmental baseline study in the Canadian Beaufort Sea, to determine the applicability of active acoustic monitoring (AAM) for marine mammal detection by comparing marine mammal observer (MMO) visual sightings and active acoustic detections. During 170 h of simultaneous MMO and AAM, 115 bowhead whales ( Balaena mysticetus ) and four beluga whales ( Delphinapterus leucas ) were visually sighted by MMOs, while 59 sonar detections of bowhead whales occurred using AAM. The fisheries sonar detected 92% of the cetaceans observed within 2, 000 m. Additional observations of ringed seals ( Pusa hispida ) and bearded seals ( Erignathus barbatus ) were recorded both by MMOs and AAM. Comparative results indicate that a commercially available active acoustic system can consistently detect marine mammals within varying ranges dictated by water column properties. Shallow environments and strong pycnoclines currently present challenges to AAM.